Biomechanical investigation of a minimally invasive posterior spine stabilization system in comparison to the Universal Spinal System (USS). Issue 1 (December 2016) - Kubosch, D.; Kubosch, E.; Gueorguiev, B.; Zderic, I.; Windolf, M.; Izadpanah, K.; Südkamp, N.; Strohm, P.
Abstract Background Although minimally invasive posterior spine implant systems have been introduced, clinical studies reported on reduced quality of spinal column realignment due to correction loss. The aim of this study was to compare biomechanically two minimally invasive spine stabilization systems versus the Universal Spine Stabilization system (USS). Methods Three groups with 5 specimens each and 2 foam bars per specimen were instrumented with USS (Group 1) or a minimally invasive posterior spine stabilization system with either polyaxial (Group 2) or monoaxial (Group 3) screws. Mechanical testing was performed under quasi-static ramp loading in axial compression and torsion, followed by destructive cyclic loading run under axial compression at constant amplitude and then with progressively increasing amplitude until construct failure. Bending construct stiffness, torsional stiffness and cycles to failure were investigated. Results Initial bending stiffness was highest in Group 3, followed by Group 2 and Group 1, without any significant differences between the groups. A significant increase in bending stiffness after 20'000 cycles was observed in Group 1 (p  = 0.002) and Group 2 (p  = 0.001), but not in Group 3, though the secondary bending stiffness showed no significant differences between the groups. Initial and secondary torsional stiffness was highest in Group 1, followed by Group 3 and Group 2, with significant differences between all groups (p  ≤ 0.047). A significant increase in initial torsional stiffness after 20'000 cycles was observed in Group 2 (p  = 0.017) and 3 (p  = 0.013), but not in Group 1. The highest number of cycles to failure was detected in Group 1, followed by Group 3 and Group 2. This parameter was significantly different between Group 1 and Group 2 (p  = 0.001), between Group 2 and Group 3 (p  = 0.002), but not between Group 1 and Group 3. Conclusions These findings quantify the correction loss for minimally invasive spine implant systems and imply that unstable spine fractures might benefit from stabilization with conventional implants like the USS.